Mechanisms of Action of and Cellular Resistance to Chemotherapeutic Agents in Human Cells: Possible Applications to Quantitative Mutagenesis - Murray, W. (My University, 1986)
The aim of this study was to investigate the mechanisms of action of and development of cellular resistance to various anticancer agents in human (HeLa) cells using a combined genetic and biochemical approach. The agents employed for this purpose included: the purine nucleoside analogues, toyocamycin, tubercidin, and 6-methyl-mercaptopurine riboside (6-MeMPR); the protein synthesis inhibitor, puromycin; and the microtubule stabilizer, taxol. To investigate the mechanisms of action and cellular resistance to the purine nucleoside analogues, stable first-step toyocamycin, tubercidin and 6-MeMPR resistant HeLa mutants were isolated. These mutants exhibited high degrees of resistance and cross-resistance to various adenosine kinase-activated nucleoside analogues, possessed <2% of the adenosine kinase activity of parental HeLa cell extracts and exhibited severely reduced cellular uptake and macromolecular incorporation of adenosine in vivo. These results indicate that in human cells the cytotoxic effects of toyocamycin, tubercidin and 6-MeMPR are dependent upon adenosine kinase-catalyzed phosphorylation of these drugs to their respective monophosphates and that resistance to these agents results from a deficiency in adenosine kinase activity in vivo. Further insight into the nature of the genetic and biochemical alteration(s) affecting adenosine kinase in these mutants was achieved using SDS-polyacryamide gel electrophoretic and immunoblot analysis. Immunoblots -revealed that each toyocamycin, tubercidin and 6-MeMPR resistant mutant contained similar amounts of cross-reacting material that had the same electrophoretic mobility as adenosine kinase in parental HeLa cells. Therefore, the lesion in these mutants must be a missense type of alteration in the structural gene for adenosine kinase. The utility of the 6-MeMPR resistant mutant selection system for quantitative mutagenesis studies was also investigated. Numerous favourable attributes appropriate to mutagenesis studies were found using this selection system. These included: the obtainment of highly resistant mutants which were stable in the absence of drug, the absence of cell density or cross-feeding effects in the selection system, maximum phenotypic expression required a relatively short time period and mutagen treatment increased the mutant frequency in a linear dose-dependent manner. Thus, selection for genetic alterations at the adenosine kinase locus appears to provide a valuable system for quantitative mutagenesis studies in human cells. The combined genetic and biochemical approach was also used to investigate the development of resistance to puromycin and taxol. Therefore, first-and second-step mutants resistant to each of these drugs were selected and characterized. Cross-resistance and uptake studies with the puromycin resistant mutants suggest that the most common -mechanism for the development of cellular resistance to puromycin in human (HeLa) cells involves an alteration in membrane permeability that reduces drug uptake/transport. Similar studies with the taxol resistant mutants suggest the existence of two possible mechanisms for the development of resistant to this agent in human (HeLa) cells. One mechanism involves a biochemical lesion that specifically affects a microtubule-related cellular component. The second mechanism, however, nonspecifically affects cellular membrane permeability and results in reduced drug uptake/transport.
Mechanisms of Action of and Cellular Resistance to Chemotherapeutic Agents
Keywords: cell; resistance; chemotherapy; human; mutagenesis